2016
DOI: 10.1007/s11367-016-1078-9
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of construction and renovation of sewer systems using a detailed inventory tool

Abstract: 10Purpose: The objective was to provide comprehensive life cycle inventories for the construction and renovation 11 of sewers. A detailed inventory was provided with multiple options of pipe materials, diameters and site-specific 12 characteristics, and was embedded into an Excel®-based tool. The tool allows for life cycle evaluation of 13 different sewers. It was applied to determine the most important phases, processes and related parameters 14 involved in the construction and renovation of sewers from an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…This study found that the GWP of wastewater infrastructure was less than 2% of the global warming impact caused by the wastewater subsystem, which lies at the lower end of the reported range of 1%–30% ( Machado et al., 2007 ; Morera et al. 2016 , 2017 ; Ortiz et al., 2007 ; Renou et al., 2008 ., Risch et al., 2015 ; Vlasopoulos et al., 2006 ).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…This study found that the GWP of wastewater infrastructure was less than 2% of the global warming impact caused by the wastewater subsystem, which lies at the lower end of the reported range of 1%–30% ( Machado et al., 2007 ; Morera et al. 2016 , 2017 ; Ortiz et al., 2007 ; Renou et al., 2008 ., Risch et al., 2015 ; Vlasopoulos et al., 2006 ).…”
Section: Resultsmentioning
confidence: 83%
“…Various data sources including the existing ecoinvent database, equipment designs, manufacturer and supplier questionnaire responses, and real information from existing systems were utilized to estimate life cycle environmental impacts of infrastructure. This study, along with two previous studies ( Morera et al. 2016 , 2017 ), collected detailed information on construction materials, equipment, devices, and civil works for wastewater infrastructure.…”
Section: Resultsmentioning
confidence: 99%
“…Burning plastic waste such as PVC and HDPE pipes leads to emissions of volatile organic compounds, polycyclic aromatic hydrocarbons, sulfur oxides, and large amounts of greenhouse gases, which increase the GWP (Al-Salem, Lettieri, and Baeyens 2009; Antelava et al 2019). The heating value of the incineration of HDPE is 41.84 MJ/kg, which is two times greater than that of PVC (Morera et al 2016). Therefore, as shown in Figure 4(a), the energy recovery from burning HDPE pipes can offset the adverse effects of incineration impacts associated with the CED indicator.…”
Section: Environmental Impacts Associated With the Renovation Stage Of Plastic Pipesmentioning
confidence: 98%
“…They indicated that 41% of global warming potential and 43% of energy consumption of the entire UWS were related to the operation and maintenance phase of the WDN. In contrast, some researchers have only focused on specific parts of UWSs, such as WWTPs (Awad, Alalm, and El-Etriby 2019;Garfí, Flores, and Ferrer 2017), WDNs (Sanjuandelmás et al 2014;Piratla et al 2012), and WWCs (Morera et al 2016;Vahidi et al 2016), to elucidate the significance of inventory data and compare the environmental impacts caused in different LCA phases. Risch et al (2015) conducted a comprehensive LCA for sewer systems and WWTPs considering the construction and operation phases.…”
Section: Introductionmentioning
confidence: 99%
“…Within the existing literature, articles have mainly focused on the environmental impacts of the construction or full life cycle of sewers (Morera et al. ; Vahidi et al. , ; Petit‐Boix et al.…”
Section: Introductionmentioning
confidence: 99%